Wartości etyczne a determinanty ekonomiczne - spór o kształt systemu zarządzania służbą zdrowia = Ethical values and economic determinants - a dispute over the shape of health care management system - Janusz Sytnik-Czetwertyński (Kazimierz Wielki University, 2017)
Sytnik-Czetwertyński Janusz. Wartości etyczne a determinanty ekonomiczne - spór o kształt systemu zarządzania służbą zdrowia = Ethical values and economic determinants - a dispute over the shape of health care management system. Journal of Education, Health and Sport. 2016;6(11):87-97. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164028 http://ojs.ukw.edu.pl/index.php/johs/article/view/3966       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 31.10.2016.       Wartości etyczne a determinanty ekonomiczne - spór o kształt systemu zarządzania służbą zdrowia Ethical values and economic determinants - a dispute over the shape of health care management system   Janusz Sytnik-Czetwertyński   UKW w Bydgoszczy, Poland       Słowa kluczowe: zdrowie publiczne, zarządzanie wartościami, wartości etyczne, idealizm   Key words: public health, management values, ethical values, idealism     Abstrakt   Jeśli chcemy podążyć drogą odpowiedzialnej budowy systemu służby zdrowia, to skazani jesteśmy na rozwiązania idealistyczne, oparte na wartościach. Rozwiązania idealistyczną są jednak kosztowne. Zazwyczaj odnoszą się do konieczności podjęcia określonego działania bez względu na jego koszty obecne i przyszłe. Idee w ogóle nie definiują bowiem kosztów, podobnie jak zysków. Idee interesuje jedynie efekt, rozumiany jako wypełnienie określonej wartości. Skutkiem tego system taki jest z góry narażony na upadek, a jego los przesądzony. To bowiem, co nie uwzględnia codziennej praktyki staje się oderwane od rzeczywistości, niepotrzebne, zorientowane na siebie samo.   Abstract   If you want to follow the way of responsible health care system building, is stuck we are idealistic, solutions based on the values. An idealistic solutions, however, are costly. Usually refer to the need to take specific action regardless of its present and future costs. Ideas do not define because costs as profits. The ideas it interested in only the effect, understood as a fill to the specified values. The effect of such a system is vulnerable to collapse, and his fate sealed. In fact, which does not take into account the daily practice becomes detached from reality, unnecessary, oriented to each other the same thing.